Extra-intestinal findings on magnetic resonance enterography in children with inflammatory bowel disease. Issue 9 (September 2016) - Sheybani, E.F.; Sheikh, N.; Chavhan, G.B.; Greer, M.-L.C.
Abstract : Aim: To determine the occurrence of extra-intestinal findings on magnetic resonance enterography (MRE) in a large cohort of children with known or suspected inflammatory bowel disease, characterise those findings, determine the technique and frequency of follow-up imaging, and associated costs. Materials and methods: Imaging reports from 757 MRE examinations in 671 children with known or suspected IBD from 2011 through 2012 were analysed retrospectively. Reported extra-intestinal findings were categorised by two radiologists in consensus as normal, normal variants or commonly seen findings without clinical significance, or abnormal. Prior imaging reports of the patients with abnormal findings were reviewed to identify which findings were new or substantially changed. Subsequent imaging examinations, their associated costs, and additional work-up of extra-intestinal findings were recorded in each group. Results: A total of 403 extra-intestinal findings were reported in 290 MRE (38.3%) examinations performed in 269 children (40.1%). Of these, 189 (46.9%) findings were abnormal and new or significantly changed from prior imaging, 88 (21.8%) were abnormal and stable, 50 (12.4%) were normal variants or commonly seen findings with no clinical significance, and 76 (18.9%) were normal. Abnormal findings included 34.7% associated with IBD and 65.3% considered unrelated. Follow-up imaging was performed for 69 (17.1%) mostly abnormal findings in 94 patients (8.3%). Magnetic resonance imaging (51%) and ultrasound (28%) were the most commonly utilised imaging methods. Conclusion: MRE identifies a large number of previously unknown extra-intestinal abnormalities in children with known or suspected IBD, most unrelated to IBD. Although <10% of children having MRE undergo subsequent imaging of extra-intestinal abnormalities, given the rapid uptake of MRE in the paediatric population, emphasis should be given to avoiding techniques utilising ionising radiation at follow-up. Highlights: We examined frequency of extra-intestinal findings on MRE in children with IBD. Abnormal extra-intestinal findings were common, most previously unknown. Few underwent further imaging, usually without ionizing radiation. Imaging costs and work-up of extra-intestinal findings on MRE were also discussed.